Synthesis and characterization of GaN/ReS2, ZnS/ReS2 and ZnO/ReS2 core/shell nanowire heterostructures - Butanovs, Edgars; Kuzmin, Alexei; Piskunov, Sergei; Smits, Krisjanis; Kalinko, Aleksandr; Polyakov, Boris (Elsevier B.V., 2021)
Layered 2D van der Waals (vdW) materials such as graphene and transition metal dichalcogenides have recently gained a great deal of scientific attention due to their unique properties and prospective applications in various fields such as electronics and optoelectronics, sensors and energy. As a direct bandgap semiconductor in both bulk and monolayer forms, ReS2 stands out for its unique distorted octahedral structure that results in distinctive anisotropic physical properties; however, only a few scalable synthesis methods for few-layer ReS2 have been proposed thus far. Here, the growth of high-quality few-layer ReS2 is demonstrated via sulfurization of a pre-deposited rhenium oxide coating on different semiconductor material nanowires (GaN, ZnS, ZnO). As-produced core-shell heterostructures were characterized by X-ray diffraction, scanning and transmission electron microscopy, micro-Raman spectroscopy and X-ray absorption spectroscopy. Experimental characterizations were supported by total energy calculations of the electronic structure of ReS2 nanosheets and GaN, ZnS, and ZnO substrates. Our results demonstrate the potential of using nanowires as a template for the growth of layered vdW materials to create novel core-shell heterostructures for energy applications involving photocatalytic and electrocatalytic hydrogen evolution.
This research was funded by the ERDF project “Smart Metal Oxide Nanocoatings and HIPIMS Technology”, project number: 1.1.1.1/18/A/073. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART².
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; ReS2; Layered materials; Core-shell nanowire; Electron microscopy; X-ray diffraction; Raman spectroscopy; X-ray absorption spectroscopy